Immune Hematology Diagnosis and Management of Autoimmune Cytopenias (Springer International Publishing, 2018)
This text provides a concise yet comprehensive overview of the most common autoimmune cytopenias affecting adults and children. The book is divided into four sections, each of which focuses on a major autoimmune cytopenia. The first section features background, pathophysiology, presentation, evaluation, and treatment strategies for immune thrombocytopenia (ITP), the most common cause of antibody-mediated platelet destruction. The second section reviews common forms and treatment strategies for autoimmune hemolytic anemia (AIHA), including a chapter dedicated specifically to Evans Syndrome. The third section comprehensively reviews the pathophysiology, diagnosis and current management approaches to thrombotic thrombocytopenic purpura (TTP), a potentially life-threatening autoimmune syndrome. The book concludes with a final section on autoimmune neutropenia. Each section includes a review of common underlying systemic autoimmune conditions and immune deficiency syndromes that can accompany or cause autoimmune cytopenias. Written by experts in each content area, Immune Hematology: Diagnosis and Management of Autoimmune Cytopenias is a valuable resource for clinicians and professionals who treat patients afflicted with autoimmune cytopenias, including primary care providers, hematologist/oncologists, immunologists, among others.